"Madness" and penal confinement: Some observations on mental illness and prison pain. (July 2017) - Haney, Craig
Unprecedented numbers of mentally ill persons are now housed in prisons and jails in the United States and elsewhere in the world. In many jurisdictions penal institutions have become the default placement for the mentally ill, in lieu of more humane and appropriate facilities in which to treat them. This article briefly reviews some of the causes of the unprecedented influx of the mentally ill into prisons and jails, examines the characteristics of these environments that render them singularly inappropriate placements in these cases, and discusses the various ways that the pains of imprisonment can exacerbate rather than alleviate various forms of mental illness and psychological vulnerability.